Plasminogen Depletion during Administration of Epsilon-aminocaproic Acid - Nibbelink, D. W; Jacobsen, C. D (Thrombosis and Haemostasis, 1973)
Sixteen patients with acute onset subarachnoid hemorrhage were treated with intravenous administration of epsilon-aminocaproic acid. This drug inhibits activation of plasminogen and, to some extent, the effect of plasmin as well. In this study a marked decrease in immunological quantities of plasminogen was observed. This depletion of plasminogen occurred without concommitant quantitative changes in platelets or fibrinogen. Hence, the antiftbrinolytic effect of epsilon-aminocaproic acid is not only through inhibition of plasminogen activation and of plasmin itself, but also through a marked reduction in plasminogen.